Studies on the Effect of Plasminogen Activator on the Interaction between α2-Macroglobulin and Plasmin - Toki, Naotika; Takasugi, Sumiyoshi; Sumi, Hiroyuki; Yamura, Takuso (Thrombosis and Haemostasis, 1978)
Six different plasmins were prepared by incubating human plasminogen with various amounts of streptokinase or urokinase. It was confirmed that the six different plasmins possessed similar caseinolytic activities, and the inhibitory effects of α 1-antitrypsin on caseinolytic activities of the six different plasmins were all the same. On the other hand, interactions between the six different plasmins and α2-macroglobulin were complicated. Plasmins activated by cleavage of plasminogen were almost immediately or effectively inhibited by α2-macroglobulin. However, plasmin activated by complex formation of plasminogen with streptokinase was not so immediately or effectively inhibited by α2- macroglobulin. It was supposed that the difference between these two results on the interaction between plasmin and α2-macroglobulin might be due to the difference in molecular form of plasmin. In the present study, it was also confirmed that streptokinase or urokinase, in free form in the reaction mixture, interfered with the interaction between plasmin and α2-macroglobulin. The cause for such interference was discussed.